The Complete Subjective Health Assessment - Lapum, Jennifer L.; St-Amant, Oona; Hughes, Michelle (Open textbook library., 2019)
This textbook is designed for the novice learner who is seeking to develop a foundational understanding of the complete subjective health assessment in the context of health and illness. The textbook deconstructs the categories of the complete subjective health assessment, providing learners with explanations and examples of what constitutes relevant subjective data. This textbook provides an opportunity to learn how to respond to normal, abnormal, and critical findings when completing a complete subjective health assessment